2021
DOI: 10.24875/bmhim.20000216
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection in a pediatric patient with cystic fibrosis

Abstract: Background: Cystic fibrosis (CF) is a potentially mortal disease characterized by a chronic pulmonary disease with persistent airway infection. Children with this disease are more susceptible to respiratory infections due to the limitation in mucociliary transport and anatomical disruption of the bronchial tree. SARS-CoV-2 causes COVID-19, a respiratory illness related to exacerbations of chronic pulmonary pathologies in children, such as CF and asthma. There are not enough case reports on pediatric patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…A total of 31 papers published as observational studies reported an association of COVID-19 in patients with CF [ 18 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] ( Table 1 ). These studies comprised 661,386 patients in total, including children, adults, and elderly age groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 31 papers published as observational studies reported an association of COVID-19 in patients with CF [ 18 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] ( Table 1 ). These studies comprised 661,386 patients in total, including children, adults, and elderly age groups.…”
Section: Resultsmentioning
confidence: 99%
“…However, only 19,150 (2.9%) patients were diagnosed with CF and, from these patients, 2523 (0.4%) were diagnosed with both CF and COVID-19. Regarding patients with CF and COVID-19, the sex proportion was (female/male) 1207/1167 [ 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 45 , 47 , 48 , 49 , 50 ]. Some publications [ 21 , 26 , 35 , 40 , 46 ] did not report the sex of the patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porém, a infecção pode apresentar apenas uma doença de grau leve em alguns casos rinofaringite viral -resfriado (PECKHAM et al, 2020;PÁEZ-VELÁSQUEZ et al, 2021).…”
Section: Introductionunclassified
“…O primeiro caso relatado da doença pelo coronavírus surgiu na cidade de Wuhan, na China, no dia 31 de dezembro de 2019, e rapidamente esse vírus se proliferou, acarretando uma pandemia. Os coronavírus fazem parte da família Coronaviridae e possuem elevada habilidadede transformação e rearranjo genético (PÁEZ-VELÁSQUEZ et al, 2021).…”
Section: Introductionunclassified